Civility, Trust, and Responding to Echo Chambers. (December 2021) - Rodrigues, Daniel
Abstract: Due to the rampant epistemic distrust present in echo chamber members towards outsiders, responding to echo chambers with civil debate is unlikely to lead to any agreement or compromise. Moreover, a civil response may contribute to the echo chamber's inflated sense of epistemic status, which is precisely what needs to be dismantled or diminished if agreement/compromise is to be made possible. When responding to particularly dangerous and resistant echo chambers, a moderately uncivil response may be warranted.